Karakteristik Kimia dan Mikrostruktur Otot Longissimus Dorsi dan Biceps Femoris dari Sapi Glonggong (Chemical Characteristics and Microstructure of Longissimus Dorsi and Biceps Femoris Muscle of Glonggong Beef Cattle) - Amrih Prasetyo; Soeparno (Soeparno); Edi Suryanto; Rusman (Rusman) (Buletin Peternakan, 2009)
The study was conducted to evaluate chemical and microstructure characteristics of glonggong (excessive drink) meat compared with the normal meat. The meat samples were taken from Boyolali Regency, came from five glonggong male Ongole grade cattle, and from five normal cattle with the average life weight of 250–300 kg. The chemical data were analyzed by using analysis of variance of 2x2 factorial patterns. The microstructure characteristics were also analyzed descriptively. The water content of glonggong meat was higher compared with that of normal meat on BF and LD muscle, average water content was 80.64% and 80.14% vs 78.60% and 74.57%, respectively. The protein contents of BF (15.98%) and LD (16.17%) was lower than the protein contents normal meat of BF (21.08%) and LD (21.07%), respectively. The Result of statistical analyzed shows significant pengglonggongan of cattle before slaughtered (P<0.05) to meat fat value at every muscle. The meat lactic acid value of glonggong meat of LD muscle was lower than that of normal meat of LD muscle (2815.891 vs 6827.77 ppm). There was a damage of glonggong meat microstructure of LD, BF muscle and also of liver organ. In conclusion, glonggong meat had a lower chemical characteristics compared with the normal meat.(Key words: Chemical, Microstructure, Meat, Glonggong)